2001
DOI: 10.1097/00007632-200102010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Percutaneous Intradiscal Radiofrequency Thermocoagulation for Chronic Discogenic Back Pain

Abstract: Percutaneous intradiscal radiofrequency thermocoagulation (90 seconds, 70 C) is not effective in reducing chronic discogenic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 25 publications
1
126
1
2
Order By: Relevance
“…One RCT compared the effects of IRFT denervation (N=13 patients) and sham IRFT (same procedure but without the use of radiofrequency current ; N=15) on shortterm pain relief physical impairment, disability and quality of life (Barendse 2001). There were no differences in outcome between the groups (no relevant improvements in either group).…”
Section: Effectiveness Of Irft or Idet Vs A Sham Proceduresmentioning
confidence: 99%
“…One RCT compared the effects of IRFT denervation (N=13 patients) and sham IRFT (same procedure but without the use of radiofrequency current ; N=15) on shortterm pain relief physical impairment, disability and quality of life (Barendse 2001). There were no differences in outcome between the groups (no relevant improvements in either group).…”
Section: Effectiveness Of Irft or Idet Vs A Sham Proceduresmentioning
confidence: 99%
“…On the one hand, Leclaire et al reported that the procedure is effective in terms of pain improvement only in the short term (4 weeks after the procedure) and the improvement failed to last even beyond 12 weeks [8]. Other studies supported these data, including one recently published in the Lancet [1,6,8]. On the other hand, other authors showed long-term improvement in pain even for years after the procedure [4,17,19,22].…”
Section: Introductionmentioning
confidence: 97%
“…The principle is production of heat in order to damage some or all nerve fibers in the target nervous structure (in the case of "conventional" RF) or application of an electromagnetic field to the nervous structure (in the case of pulsed RF), with the ultimate aim of blocking transmission of pain stimuli from peripheral receptors to the central pain structures. In recent years, some publications have reported contradictory results following RF treatment of back pain [1,4,6,8,17,19,22]. On the one hand, Leclaire et al reported that the procedure is effective in terms of pain improvement only in the short term (4 weeks after the procedure) and the improvement failed to last even beyond 12 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…26 With the help of thermal imaging, the temperature on the end plates does not exceed 40°C, and the temperature in the spinal canal never exceeds above 42°C even after continuous energy delivery for 30 seconds, 19 which does not have any destructive effect on the spinal cord. 27,28 From a biological point of view, it is postulated that there is the alteration of expression of inflammatory cytokines and prostaglandins in degenerated disc with the help of this heat generated by higher frequency. 29,30 The reliability and effectiveness of this technology has been demonstrated in more than 50,000 endoscopic interventions worldwide.…”
Section: Discussionmentioning
confidence: 99%